2007
DOI: 10.4081/ijas.2007.19
|View full text |Cite
|
Sign up to set email alerts
|

Butyric acid glycerides in the diet of broiler chickens: effects on gut histology and carcass composition

Abstract: Aim of the study was to verify the effects of butyric acid glycerides, as a supplemental ingredient in the diet, on live performance of broiler chickens and on the morphology of their small intestine, since short chain fatty acids are known as selective protection factors against intestinal microbial parasites, potent growth promoters of the gut wall tissues, also in terms of immune modulation response. An experiment was carried out on 150 Ross 308 female chickens, allotted to 5 treatments, over a 35 d ays per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
76
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 6 publications
16
76
2
Order By: Relevance
“…Mansoub (2011) reported that dietary sodium butyrate increased the weight gain and FCR up to 28 days of age. (Antongiovanni et al, 2007;Leeson et al, 2005;Taherpour et al, 2009). Similarly, butyric acid enhanced the weight gain and FCR (Panda et al, 2009).…”
Section: Dissociation and Absorption Of Butyric Acidmentioning
confidence: 85%
See 2 more Smart Citations
“…Mansoub (2011) reported that dietary sodium butyrate increased the weight gain and FCR up to 28 days of age. (Antongiovanni et al, 2007;Leeson et al, 2005;Taherpour et al, 2009). Similarly, butyric acid enhanced the weight gain and FCR (Panda et al, 2009).…”
Section: Dissociation and Absorption Of Butyric Acidmentioning
confidence: 85%
“…Adil et al (2010) reported that dietary butyric acid (3% application rate) significantly increased the villus height in the duodenum and jejunum only. Similarly, many researchers have described the beneficial effect of dietary sodium butyrate on villi height and crypt depth in broilers at different phases of their growth (Antongiovanni et al, 2007;Mallo et al, 2012;Panda et al, 2009;Sayrafi et al, 2011;Smulikowska et al, 2009). On the contrary, some researchers did not find any effect of dietary sodium butyrate on villi height and crypt depth (Leeson et al, 2005).…”
Section: Gut Morphologymentioning
confidence: 89%
See 1 more Smart Citation
“…Previous experiments of ours (Leeson et al, 2005;Antongiovanni et al, 2007) indicated that the effect of butyrate on the birds' gut is at the maximum level within the first two weeks. This is the reason why the results relative to 14 days are reported in Table 4 as the performance of the starter period.…”
Section: Resultsmentioning
confidence: 99%
“…The mono-, di-and tri-glycerides of butyric acid are to be preferred because easily absorbable and practically odourless. A blend of butyric glycerides produced very good results in previous trials with broilers (Leeson et al, 2005;Antongiovanni et al, 2007). The subject of the present study is the effect on the performance of broiler chickens of the monoglyceride of butyric acid (MB), as the unique butyric glyceride supplemented into the diet of broilers, possibly more efficient than the previously tested blend, because more easily absorbable.…”
Section: Introductionmentioning
confidence: 94%